Learning a lesson from Taiwan? A comparison of changes and continuity of labour policies in Taiwan and China - Lee, Chun-Yi (German Institute of Global and Area Studies / Leibniz-Institut für Globale und Regionale Studien, 2014)
This paper argues that the comparison of labour policies in Taiwan and China has an important bearing on the interaction between state and society. The fact that labour policies have changed over time illustrates a process of bargaining between the state and society. The core question of this paper is whether the development of labour policies in Taiwan can provide China a good example to learn from. In order to answer this question more systematically, the first part of this paper provides theoretical reviews of the state–society relationship, while the second part aims to verify whether those labour-favouring policies in Taiwan have changed under a different party’s governance. The third part of the paper further investigates labour policy in China; this section mainly focuses on the historical background to the new labour contract law. Based on the preceding two sections’ literature review of the changing path of labour policies, the fourth section scrutinises fundamental issues reflected in the development of Taiwan’s labour policies, then compares how those issues are reflected in the case of China. The conclusion of this paper is that although Taiwan, like China, formerly had a one-party system, the changes in Taiwan’s labour policies are not completely comparable to China, though both societies had some similarities.